2021
DOI: 10.1111/1748-8583.12409
|View full text |Cite
|
Sign up to set email alerts
|

Computer use and pay for performance

Abstract: Workplace digitalisation is a pervasive phenomenon associated to an increase in wage differentials between occupations. This paper analyses the relationship between computer use and pay for performance, whose incidence has also followed a positive growth pattern. More concretely, we examined three pay‐for‐performance schemes: productivity/piece rate, team and firm pay for performance. We also investigated the mediating role of job design in this relationship. The complementarity framework perspective and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Our study found that more human-machine collaboration can help firms to improve their service quality and gain market share (Watson et al, 2018;Singh et al, 2017, € Otting andMaier, 2018). Also introducing AI encourages team cooperation and coordination within the work team (Bayo-Moriones et al, 2022;Pendharkar, 2013). On the flip side, introducing smart machines to an organization increases the complexity and uncertainty of the organizational environment (Mirowska and Mesnet, 2022) and alters the work dynamics (Ravid et al, 2020;Fleming, 2019).…”
Section: Technical Factors Perceived Usefulnessmentioning
confidence: 63%
See 1 more Smart Citation
“…Our study found that more human-machine collaboration can help firms to improve their service quality and gain market share (Watson et al, 2018;Singh et al, 2017, € Otting andMaier, 2018). Also introducing AI encourages team cooperation and coordination within the work team (Bayo-Moriones et al, 2022;Pendharkar, 2013). On the flip side, introducing smart machines to an organization increases the complexity and uncertainty of the organizational environment (Mirowska and Mesnet, 2022) and alters the work dynamics (Ravid et al, 2020;Fleming, 2019).…”
Section: Technical Factors Perceived Usefulnessmentioning
confidence: 63%
“…, 2018; Singh et al ., 2017, Ötting and Maier, 2018). Also introducing AI encourages team cooperation and coordination within the work team (Bayo-Moriones et al. , 2022; Pendharkar, 2013).…”
Section: Results Of Systematic Literature Reviewmentioning
confidence: 99%
“…small business is one that is privately held, and the owner makes all of the choices. Computerization-related changes to job design, including increased job complexity, on-the-job training, and collaboration, (Moriones et al, 2021). Small companies are vital to an economy since they usually employ a limited number of people and are not founded with a large workforce (Rahman, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…New business opportunities align with new challenges for management (Adamovic, 2018; Caprar et al., 2022; Qin et al., 2022). An important and challenging task for organisations is the design of reward systems (Amadi et al., 2021; Bayo‐Moriones et al., 2022; Nyberg et al., 2016, 2018; Park & Sturman, 2016). This task is particularly challenging for multinational organisations because employees in today's globalised business world often have different cultural backgrounds and therefore different expectations about reward allocations (Frank et al., 2015; Načinović Braje et al., 2019; Olsen, 2015; Prince et al., 2020; Scott et al., 2015).…”
Section: Introductionmentioning
confidence: 99%